2006
DOI: 10.1080/13561820600845643
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional support of mental well-being in schools: A Bourdieuan perspective

Abstract: There is increasing international concern about the mental health and well-being of school-aged children, and the school is often seen as the optimum setting to deliver interagency interventions. This paper draws on a Scottish study examining the responses of local authorities, schools and other agencies to challenging behaviour related to poor mental health. It explores the ways in which the presence of workers from other agencies had an impact on the capacity of schools to respond to such issues. In Bourdieu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 16 publications
4
26
0
Order By: Relevance
“…Lipsky, 1980). Spratt, Shucksmith, Philip, and Watson (2006) observed similar patterns. In addition, international research has shown that school social workers often lack a clear role in the school (Altshuler & Webb, 2009;Anand, 2010;Peckover, Vasquez, Van Housen, Saunders & Allen, 2012).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Lipsky, 1980). Spratt, Shucksmith, Philip, and Watson (2006) observed similar patterns. In addition, international research has shown that school social workers often lack a clear role in the school (Altshuler & Webb, 2009;Anand, 2010;Peckover, Vasquez, Van Housen, Saunders & Allen, 2012).…”
Section: Introductionsupporting
confidence: 70%
“…In schools, the pupil healthcare organisation seems to have this function with the aim of creating an environment that promotes pupils' learning, development, and health (Socialstyrelsen, 2014). Nonetheless, this study shows that tensions can emerge between teachers' expectations to be able to hand over problems and to get emotional support from the school social worker and school social workers' desire to first of all represent and support the child (Hjelte, 2005;Spratt, Shucksmith, Philip, and Watson, 2006). A general pattern is that teachers feel that school social workers do not adequately take organisational needs into account while school social workers feel that teachers do not give enough attention to individual pupils' needs.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, my findings also confirm other research (e.g., Robinson, 2002;SlonskiFowler & Truscott, 2004;Spratt et al, 2006) that indicates that problems and pitfalls easily might arise when teachers and other professionals interact with each other and with students and their parents. By analyzing teachers, principals, nonschool situated resource team members (trained social workers and special educators), challenging students, and parents' reported experiences and representations about their interactions and collaborations, I have developed a grounded theory of collaborative synchronizing in relation to challenging students in school.…”
Section: Discussionsupporting
confidence: 80%
“…Here an "us and them" thinking had been generated in which each professional group had negative social representations or stereotypes about each other. The problems of professional boundaries, mistrust, and out-group devaluation in multiprofessional collaboration in school settings have also been shown in other studies (Meyers et al, 1996;Robinson, 2002;Slonski-Fowler & Truscott, 2004;Spratt et al, 2006).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation